Pemetaan Marker AFLP untuk Membuat Peta Genetik Bit Gula - Asep Setiawan (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2001)
One hundred eighty two AFLP marker using primer combination of EcoRI/MseI and PstI/MseI were used in this study to create a DNA marker genetic map of Sugar beet. In average each primer combination yielded 15.5 polymorphic band AFLP marker using primer combination of EcoRI/MseI significant yielded more polymorphic band  than PstI/MseI. From this study a high density DNA marker map coverage all nine chromosomes of sugar beet with  totally length of 744 cM Haldane was established. Key words: AFLP, Genetic map, Restriction enzyme, Polymorphic